2009
DOI: 10.1002/crat.200900205
|View full text |Cite
|
Sign up to set email alerts
|

A template‐free route for controlled synthesis of dumbbell‐like Sb2S3 microcrystals

Abstract: Large amounts of dumbbell-like Sb 2 S 3 microcrystals were synthesized via a simple solvothermal treatment method. Various techniques such as x-ray diffraction (XRD), field-emission scanning electron microscope (FESEM), high-resolution transmission electron microscope (HRTEM), selected area electron diffraction (SAED), and photoluminescence spectrometry (PL) have been used to characterize the obtained products. The results showed that the products belong to the orthorhombic Sb 2 S 3 phase, and the dumbbell-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Currently, synthesis and morphological control of one dimensional (1D) and 1D based complex structures of Sb 2 S 3 have been extensively focused on, and various methods have been tried to grow Sb 2 S 3 nanocrystals with different morphologies [11][12][13][14][15]. At the same time, various sulfide ion sources such as ammonium sulfide, thiourea, sodium thiosulfate and thioacetamide have been employed to synthesize Sb 2 S 3 crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, synthesis and morphological control of one dimensional (1D) and 1D based complex structures of Sb 2 S 3 have been extensively focused on, and various methods have been tried to grow Sb 2 S 3 nanocrystals with different morphologies [11][12][13][14][15]. At the same time, various sulfide ion sources such as ammonium sulfide, thiourea, sodium thiosulfate and thioacetamide have been employed to synthesize Sb 2 S 3 crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Cao et al [39] showed a broad peak centered at 2.94 eV for the as-prepared Sb 2 S 3 microspheres, and Srikanth et al [40] observed the broad emission of a dominant peak at 3.43 eV for as-deposited and annealed films of Sb 2 S 3 . Further, Xu et al [41] observed a peak at around 2.06 eV for the Sb 2 S 3 microspheres and dumbbell-like microstructures, and Alemi et al [42] recorded the emission peaks at 2.99, 2.80, and 2.61eV for synthesized Sb 2 S 3 nanorods.…”
Section: A the Characterization Of Sb 2 S 3 Thin Filmsmentioning
confidence: 96%
“…The Band Gap (E g ), Calculated Rydberg Constant (R x ), and Bohr Radius (a x ) of Free Excitons in Several Direct Gap III-V and II-VI Compound Semiconductors[41] …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the optical properties of these materials do also depend on the method of their synthesis. Though there are many reports available on the luminescence studies of group V-VI semiconductors in the literature [18], countable communications are available on Sb 2 S 3 with reference to its optical properties including photoluminescence [19][20][21]. Also, there are numerous reports on the synthesis of nanocrystalline Sb 2 S 3 [22][23][24], of which chemical solution deposition is one of the simplest and facile ways of preparing the nanocrystals of this material.…”
Section: Introductionmentioning
confidence: 99%